Survey and governance of street trees in Damaturu, Nigeria (2010)
This study examined the characteristics and management of street trees in Damaturu, the growing capital city of Yobe State, located in the Sudan savanah ecological zone of Nigeria. Enumeration of street trees was carried out in the major roads of Damaturu to identify tree species and determine population of the species. Data on the management of amenity trees in the town were collected through administration of questionnaire to forestry officials in the State’s Ministry of Environment. Data collected were analysed with descriptive statistics. The forestry field services and afforestation project units of Yobe State’s Forestry Department, in the State’s Ministry of Environment are saddled with the responsibility of managing the street trees in the city. The State’s Forestry Department has been involved with planting of trees along roads and streets since the State was created in 1991, development and management of nature’s parks for recreation since 1994 and the development and management of Greenbelt since 2003.Although there are obsolete laws and regulations guiding the use of amenity trees in Damaturu, there is yet no substantive policy document to direct the management of amenity trees in the state. Funding of street trees management in the State was generally inconsistent and inadequate between 2000 and 2010. Management of amenity trees in Damaturu enjoyed the participation of NGOs such as the Desert Shield and Yobe environmental network. Twenty tree species were identified along the major streets of the town with a total population of 2562 trees. The treescape of Damaturu has very low diversity, with Azadiracta accounting for 94.81% of the population of the street trees. Other notable tree species enumerated in order of prevalence include Polyalthia longifolia, Tamarindus indica, Piliostigma retuculata, Adansonia digitata, Acacia nilotica, Acacia sieberiana, Phoenix dactylifera, Acacia albida, Khaya senegalensis, Balanitea egyptiaca, Gmelina arborea, Eucalyptus camadulensis, Ficus platyphylla, Mangifera indica, Terminalia catappa, Albezia lebeck, Delonix regia, Ficus polita and Psidium guajava Effective street trees governance in Damaturu in particular and Yobe State in general will require the establishment of street tree unit in the state’s ministry of Environment. This unit in tandem with NGOs and other stakeholders will be responsible for mobilizing funds and members of public as well as spearheading formulation of appropriate requisite law and policy.